A comparison of scholarly productivity among current professors who obtained terminal degrees. Issue 4 (2nd October 2018) - Hollman, Angela; Bice, Matthew R.; Ball, James; Bickford, Nate; Shafer, Alex B.; Bickford, Sonja
ABSTRACT: Although scholarship is important in higher education and faculty productivity expectations are continually increasing, we still do not understand the holistic view of faculty productivity. This study takes a different viewpoint on faculty productivity examining differences by university classification and by discipline. Most importantly, we sought to obtain the effects of the delivery mode of terminal degree on later faculty productivity. The mode of terminal degree via Internet delivery looks attractive to students, but this study found that this has implications for future research productivity. These three elements illustrate a different scope that has important implications for administrative leaders looking to hire future faculty as well as students thinking about becoming a future faculty member. To capture this view, 600 faculty members from 59 American universities were surveyed. From this survey, five different variables emerged to create an overall faculty scholarly productivity factor. This factor was then compared against university classification, discipline, and mode of terminal degree. Results showed surprising significant differences between university classifications and disciplines as compared to scholarly productivity. One of the most noteworthy findings was that there is a significant difference in faculty productivity based on the mode of terminal degree. Furthermore, no difference in later faculty scholarly productivity exists between that of a hybridized, online degree and a purely online degree. Again, these results indicate significant finds which have a high influence on faculty scholarly productivity, which holds important implications for the future of the university.